2016
DOI: 10.1007/s11596-016-1594-7
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline inhibits liver fibrosis via hedgehog signaling pathway

Abstract: Infection of schistosomiasis japonica may eventually lead to liver fibrosis, and no effective antifibrotic therapies are available but liver transplantation. Hedgehog (HH) signaling pathway has been involved in the process and is a promising target for treating liver fibrosis. This study aimed to explore the effects of pentoxifylline (PTX) on liver fibrosis induced by schistosoma japonicum infection by inhibiting the HH signaling pathway. Phorbol12-myristate13-acetate (PMA) was used to induce human acute monon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The effect of PDE inhibitor, pentoxifylline, on HSC activation and trans-differentiation and the development of fibrosis was also demonstrated in In vitro and in vivo studies, supporting the role of PDE inhibition as a protective mechanism in liver fibrosis [174178]. More recently, a study demonstrated that pentoxifylline suppressed TGF-β1 expression in activated LX-2 hepatic stellate cells by inhibiting the pro-fibrogenic hedgehog signaling pathway [179]. In addition, pentoxifylline has also been reported to improve complications such as bacterial infection and renal dysfunction in patients with advanced cirrhosis [180].…”
Section: Therapeutic Interventions Via Camp Signalingmentioning
confidence: 89%
“…The effect of PDE inhibitor, pentoxifylline, on HSC activation and trans-differentiation and the development of fibrosis was also demonstrated in In vitro and in vivo studies, supporting the role of PDE inhibition as a protective mechanism in liver fibrosis [174178]. More recently, a study demonstrated that pentoxifylline suppressed TGF-β1 expression in activated LX-2 hepatic stellate cells by inhibiting the pro-fibrogenic hedgehog signaling pathway [179]. In addition, pentoxifylline has also been reported to improve complications such as bacterial infection and renal dysfunction in patients with advanced cirrhosis [180].…”
Section: Therapeutic Interventions Via Camp Signalingmentioning
confidence: 89%
“…3 D). As previously proposed for in vivo experiments 61 , 62 , we evaluated the effect of the immunomodulatory agent Pentoxifylline combined with Bz treatment. The concentrations of 0.125 mg/mL and 0.250 mg/mL did not affect cell viability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it exerts an anti-inflammatory regulation by affecting TGF-β- and tissue inhibitor metalloproteinase-1 (TIMP-1) expressions. Beneficial effects in humans with advanced liver disease have been described ( 68 ), and regulating effects of the hepatic stellate cell activity, is suggested to be related to the Hedgehog signalling pathway ( 86 ).…”
Section: Resultsmentioning
confidence: 99%